2021
DOI: 10.1002/admi.202100873
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Observations of the Manganese Porphyrin/Au Catalyst Interface Under the Electrocatalytic Process Revealed with Electrochemical Scanning Tunneling Microscopy

Abstract: O 2 + 2H 2 O + 4e − ) due to the large overpotential necessary, which remains highly interesting as a research topic. [8] Building upon studies on the rare noble metal catalysts (Pt, Ir, Ru), [9] mononuclear molecular catalysts, like metalloporphyrin, have many attractive features, including low cost, intuitive information on the reaction mechanism, and simple assembly in various energy devices, [10] prompting the improvement of the low-efficient OER catalyst. [11] However, it is still debated whether the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…EC-STM provides atomic-or molecular-level surface structures of electrocatalysts and chemical processes at the solid-liquid interface, monitoring, in operando condition, the electrocatalyst surface structures and electrode processes including , d) E app = OCP, e) E app = 0.95 V, f) E app = 1.05 V, g) E app = 1.10 V, h) E app = 1.25 V, i) E app = 0.85 V. Adapted with permission. [33] Copyright 2020, Wiley.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EC-STM provides atomic-or molecular-level surface structures of electrocatalysts and chemical processes at the solid-liquid interface, monitoring, in operando condition, the electrocatalyst surface structures and electrode processes including , d) E app = OCP, e) E app = 0.95 V, f) E app = 1.05 V, g) E app = 1.10 V, h) E app = 1.25 V, i) E app = 0.85 V. Adapted with permission. [33] Copyright 2020, Wiley.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [33] very recently reported the atomic-scale observation of a manganese porphyrin toward oxygen evolution reaction (OER). OER retains a relevant role in the development and spreading of clean energy conversion since, together with hydrogen evolution reaction (HER), it takes part to electrochemical water splitting.…”
Section: Oer At Metal Centered Porphyrins and Phthalocyaninementioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al discovered that the interaction between metalloporphyrins and the underlying Au(111) substrate results in synergistic effects on the catalytic activity for the oxygen evolution reaction. 34 Rana et al conducted research on a double decker molecule that contains phthalocyanine and observed that, on the Au(111) surface, the Au atoms bond to the double decker molecules, resulting in a significant decrease in the molecules' mobility when compared to studies conducted on a highly oriented pyrolytic graphite surface. 35 Moreover, recent studies have demonstrated that the Au(111) herringbone affects the electronic states of a TFPP porphyrin, leading to the formation of two equivalent conformations of the molecule with shifted electronic states.…”
Section: Introductionmentioning
confidence: 99%